2021
DOI: 10.1177/2325967120984139
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Severity of Juvenile Osteochondritis Dissecans in Patients With Juvenile Idiopathic Arthritis

Abstract: Background: Juvenile idiopathic arthritis (JIA) is a heterogeneous group of chronic arthritides presenting in patients aged ≤16 years, with a prevalence of 16 to 150 per 100,000. Juvenile osteochondritis dissecans (OCD) is an idiopathic disease of articular cartilage and subchondral bone, has an onset age of 10 to 16 years, and often affects the knee, with a prevalence of 2 to 18 per 100,000. Currently, there are few studies that have evaluated the relationship between JIA and OCD. Hypothesis: OCD is more prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…In addition, a recent study demonstrated that the prevalence of OCD in children with JIA is 50–500 times that of children overall. The prevalence and severity of OCD in JIA are higher than in the general population, hence JIA should be considered a risk factor for the development of OCD [15 ▪ ]. Once an OCD is identified, prompt treatment may prevent further subchondral damage or stress fracture and potentially mitigate surgical intervention [14].…”
Section: Osteochondritis Dissecans Of the Talusmentioning
confidence: 99%
“…In addition, a recent study demonstrated that the prevalence of OCD in children with JIA is 50–500 times that of children overall. The prevalence and severity of OCD in JIA are higher than in the general population, hence JIA should be considered a risk factor for the development of OCD [15 ▪ ]. Once an OCD is identified, prompt treatment may prevent further subchondral damage or stress fracture and potentially mitigate surgical intervention [14].…”
Section: Osteochondritis Dissecans Of the Talusmentioning
confidence: 99%
“…OCD is a disease occurring most commonly in children and adolescents between the ages of 10 and 20 6. OCD has a prevalence of 2 to 18 per 100,000 in the pediatric population 7. OCD includes changes in the supporting structures below articular cartilage and may lead to cartilage/bone separation and breakdown of the joint 8.…”
mentioning
confidence: 99%
“…6 OCD has a prevalence of 2 to 18 per 100,000 in the pediatric population. 7 OCD includes changes in the supporting structures below articular cartilage and may lead to cartilage/bone separation and breakdown of the joint. 8 Young males who are athletically active are at the highest risk and the cause of OCD may be connected to repetitive microtrauma.…”
mentioning
confidence: 99%